2015
DOI: 10.4338/aci-2015-04-ra-0044
|View full text |Cite
|
Sign up to set email alerts
|

Quality Outcomes in the Surgical Intensive Care Unit after Electronic Health Record Implementation

Abstract: KeywordsElectronic health records, quality improvement, critical care, surgical intensive care SummaryBackground: The electronic health record (EHR) is increasingly viewed as a means to provide more coordinated, patient-centered care. Few studies consider the impact of EHRs on quality of care in the intensive care unit (ICU) setting. Objectives: To evaluate key quality measures of a surgical intensive care unit (SICU) following implementation of the Epic EHR system in a tertiary hospital. Methods: A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Few studies report direct effects on patient outcome, most focusing on billing and efficiency, but in one intensive care unit (ICU) study, whilst there was no significant difference in length of stay or readmission rates, there was significant reduction in central-line infection and overall mortality rates 92. Similarly, another ICU study reported significantly decreased overall mortality, due to reduced medication errors 93…”
Section: Resultsmentioning
confidence: 99%
“…Few studies report direct effects on patient outcome, most focusing on billing and efficiency, but in one intensive care unit (ICU) study, whilst there was no significant difference in length of stay or readmission rates, there was significant reduction in central-line infection and overall mortality rates 92. Similarly, another ICU study reported significantly decreased overall mortality, due to reduced medication errors 93…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that there may be improvements in length of stay, mortality, inpatient rate of infections, adherence to guidelines, rate of medication errors, costs and utilization of physician time. [10][11][12][13][14][15][16] Other studies have reported that the introduction of EHR may result in less orders for unnecessary tests and imaging and can possibly influence confidence in diagnosis. 17,18 The difficulty in reaching a conclusion as to benefits of EHR is due to multiple factors, these include a wide spectrum of commercially available EHR systems, mixed taxonomy utilized by different studies, intrinsic site and utilization differences and an absence of standardized measure in the assessment of EHR performance.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Flatow and colleagues found an 85% decrease in central line associated blood stream infections per 1000 catheter days and a 28% decline in mortality within a surgical intensive care unit after the institution of an EHR; however, there were many associated confounders. [32]…”
Section: Resultsmentioning
confidence: 99%